2018
DOI: 10.3389/fmars.2018.00410
|View full text |Cite
|
Sign up to set email alerts
|

Contraction Dynamics and Respiration of Small Single-Osculum Explants of the Demosponge Halichondria panicea

Abstract: Sponges pump large amounts of seawater through their water canal system, providing both food and oxygen to the sponge body. Sponge pumping activity may show considerable variation as a consequence of contractile behavior, which includes contraction and expansion of the exhalant opening (osculum) in regular or irregular time intervals. The present study unravels short-and long-term effects of contractionexpansion events on the respiration rate of small single-osculum explants of the demosponge Halichondria pani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 60 publications
5
23
0
Order By: Relevance
“…The difference between the microbial communities in G. barretti and those in anoxia-tolerant species from Lough Hyne might be due to differences in morphology, as G. barretti is a massive species, or environment, since it occurs more under constant oxygenation than under seasonal anoxia. Thus, the "anoxic microecosystems" observed in G. barretti (49) may result from its morphology, and the thin, encrusting sponges of Lough Hyne could be comparatively more oxygenated most of the year, even if pumping ceases (91). Periods of pervasive oxygenation would restrict symbioses with obligate anaerobes and favor microbes with flexible metabolic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the microbial communities in G. barretti and those in anoxia-tolerant species from Lough Hyne might be due to differences in morphology, as G. barretti is a massive species, or environment, since it occurs more under constant oxygenation than under seasonal anoxia. Thus, the "anoxic microecosystems" observed in G. barretti (49) may result from its morphology, and the thin, encrusting sponges of Lough Hyne could be comparatively more oxygenated most of the year, even if pumping ceases (91). Periods of pervasive oxygenation would restrict symbioses with obligate anaerobes and favor microbes with flexible metabolic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Reiswig found that sponge-pumping behavior was more complex than previously thought and might be driven by both abiotic (e.g., storms, sedimentation, and temperature) and intrinsic factors (e.g., daily cycles and behavioral pattern). More recent studies focused on the effect of a single parameter on the sponge pumping in either laboratory conditions (e.g., Annandale, 1907;Stuart and Klumpp, 1984;Huysecom et al, 1988;Riisgård et al, 1993;Larsen and Riisgård, 1994;Tompkins-MacDonald and Leys, 2008;Pfannkuchen et al, 2009;Schläppy et al, 2010;Massaro et al, 2012;Lavy et al, 2016;Strehlow et al, 2016;Kumala et al, 2017;Kumala and Canfield, 2018;Goldstein et al, 2019) or in situ (e.g., Gerrodette and Flechsig, 1979;Savarese et al, 1997;Bell et al, 1999;Trussell et al, 2006;Tompkins-MacDonald and Leys, 2008;Schläppy et al, 2010;Leys et al, 2011;McMurray et al, 2014;Lewis and Finelli, 2015;Ludeman et al, 2017;Grant et al, 2019;Wooster et al, 2019). Unfortunately, most studies were short term or small scale and thereby failed to provide a comprehensive view of the long-term in situ natural pumping behavior of the studied sponges.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the microbial communities in G. barretti compared to anoxic-tolerant species from Lough Hyne could be due to differences in morphology as G. barretti is a massive species, or environment, since it is found under more or less constant oxygen rather than seasonal anoxia. Thus, the 'anoxic micro-ecosystems' observed in G. barretti (49) may result from its morphology, and the thin, encrusting sponges of Lough Hyne could be comparatively more oxygenated most of the year, even if pumping ceases (90).…”
Section: Sponge Diversity At a Seasonally Anoxic Sitementioning
confidence: 99%